Forma política e a crítica ao Estado em Marx - Oliveira, Isabela Alline (Universidade Federal de São Carlos, 2019)
This work intends to investigate Marx’s critique of the State and how starting with this critique the author establishes a presupposition to think the political forms of organization of society according to the true democracy (wahre Demokrastie) as condition to think the idea of emancipation. Therefore the notions of revolution and historical-dialectical materialism are fundamental elements for reflecting the dichotomy between State and civil society characteristic of modern society for the author.
Keywords: Estado; Forma política; Marx; State; Political forms; CIENCIAS HUMANAS::FILOSOFIA